Intratunical instillation of bupivacaine and methylprednısolone for relief of scrotal pain and swelling from tese or mesa - Erdogru, Tibet; Akyol, Esra; Tosun, Süleyman; Bayazıt, Numan (My University, 2001)
Objective: Scrotal pain and swelling due to surgical sperm retrieval procedures and peritesticular fibrosis, as a problem of late term, create significant morbidity in the postoperative life of patients and affect possible future sperm retrieval procedures. Methods: Thirty-one patients received NSAIDS postoperatively by IM (intramuscular) route without local anaesthetic agent and/or corticosteroid instillation around the testicles before closure of the tunica vaginalis-control group-. No NSAIDS were given to the remaining 34 patients in whom 2.5 ml of 0.5% bupivacaine combined with 10 mg/ml. methylprednisolone were introduced before closing of the tunica vaginalis. The mean pain scale scores and duration of painless period after surgery between the two groups were evaluated. Results: The mean pain score difference was not statistically significant just after surgery between the two groups (p>0.05), while the differences were significant for 2 and 4 hours after surgery (p<0.05 and p<0.01). The mean duration of pain free interval (hours) after the procedure was 47.8 ± 16.9 (12-72) hours in the intratunical instillated group patients, and 10 (29%) and 23 (67%) of them were completely free of pain and had no scrotal swelling, respectively. Meanwhile, in the control group, the mean painless period was 9.9 ± 3.6 (4-20) hours, after second NSAID, and 30 of them (97%) had scrotal swelling, postoperatively. Conclusion: This study confirms that direct intratunical Instillation of bupivacaine and methylprednisolone around the testis reduces postoperative pain, scrotal swelling and peritesticular fibrosis. Controlling of post surgical scrotal pain and edema results in more rapid return to daily activities and work.
Keywords: ICSI, Pain, Scrotum, Surgical sperm retrieval, Testis